2022
DOI: 10.1051/0004-6361/202142916
|View full text |Cite
|
Sign up to set email alerts
|

The dawn of a new era for dustless HdC stars withGaiaeDR3

Abstract: Context. Decades after their discovery, only four hydrogen-deficient carbon (HdC) stars were known to have no circumstellar dust shell. This is in complete contrast to the ∼130 known Galactic HdC stars that are notorious for being heavy dust producers, i.e. the R Coronae Borealis (RCB) stars. Together they form a rare class of supergiant stars that are thought to originate from the merger of CO/He white dwarf (WD) binary systems, otherwise known as the double degenerate scenario. Aims. We searched for new dust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 116 publications
3
3
0
Order By: Relevance
“…In addition, dLHdC stars have lower absolute magnitudes than RCB stars with the same color and shorter pulsation periods (Tisserand et al 2022), which as our models show, hints that dLHdC stars may have lower masses. If true, then dLHdC stars are ideal for studying pulsations in HdC stars, not just because they do not show dust ejection episodes but also because nonadiabatic effects are less important.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…In addition, dLHdC stars have lower absolute magnitudes than RCB stars with the same color and shorter pulsation periods (Tisserand et al 2022), which as our models show, hints that dLHdC stars may have lower masses. If true, then dLHdC stars are ideal for studying pulsations in HdC stars, not just because they do not show dust ejection episodes but also because nonadiabatic effects are less important.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, the inferred number of galactic RCB stars (e.g., Tisserand et al 2020) is broadly consistent with that expected from the He WD-CO WD merger rate (e.g., Ruiter et al 2009;Karakas et al 2015), whereas the final flash stars spend too little time in the RCB phase to explain the number of known RCB stars (Clayton et al 2006). It has been suggested that dLHdC stars are similarly formed through mergers but with different mass ratios (e.g., Karambelkar et al 2022;Tisserand et al 2022).…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations